La Senior Recurso de San Juan : Heritage Resort of San Juan - Barcelon, Paul Marlon T. (Manila : National University, 2014)
In this proposal, the legacy of our forefathers and the beautiful Filipino traditions live on. It is a step back into the past, reliving the age- old traditions and practices distinct to our culture, without leaving the luxury and comforts of the modern world.
Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Suggestions, corrections & Final revisions -- Bibliography -- Annexes.
Includes bibliographical references.
Keywords: HERITAGE RESORT